Correção logarítmica no potencial newtoniano e sua aplicação a galáxias espirais - Campos, Juliano Pereira (2007)
A well elaborated characterization of the masses of the galaxies is of basic importance to understand the formation and the evolution of the galaxies, as well as the Universe. The circular speed of the spiral galaxies is used to estimate the mass of the galaxies. The observacional data of the rotation curves exactly show that the circular speeds practically remain constant at large distances of the galactic center, where the influence of the luminous mass is very attenuated. With this observacional evidence, of originates one of the controvertial problems of astrophysics galactic and the extra-galactic: what it could cause this phenomenon? Some researchers try to solve the problem of the flattenning of the rotation curves adding one extra component of mass, the dark matter; other researchers consider a correction in the Newtonian gravitational potential. We present in this work, a logarithmic correction in the Newtonian gravitational potential as an alternative for the explanation of the problem of the flattenning of the rotation curves without the necessity to add dark matter. Moreover, the logarithmic structure of the correction opens possibility of connection with the theory of cosmic strings. Although the use of a simplified disk mass distribution, the obtained analytical results in the present work show to an excellent agreement with the observational data of the curves of rotation of the majority of analyzed galaxies LSB. These results stimulate to invest in the sophistication of the model